Сomparative analysis between electronic dictionaries and traditional dictionaries - Shakhnoza Sultanova (Genius Journals, 2023)
This article will discuss in detail the differences between electronic dictionaries and traditional dictionaries. At the same time, the role of electronic dictionaries in the computerized society, convenience, development stages are also covered. The stages of creating an electronic dictionary are covered in detail. Integrating the electronic dictionary into artificial intelligence creates a basis for easy and convenient learning of Uzbek language terms by different peoples at the international level. Also, reflecting the words characteristic of our national terminology in the dictionary can have a positive effect on the terminology of the neighboring nations, and can be a resource for use.
Keywords: electronic dictionary; traditional dictionary; lexicography; lemma